Representation of Beauty Standard on Indonesia’s Woman Bankers - Sofy Fawzia Munafidsyah; Sri Kusumo Habsari; Ismi Dwi Astuti Nurhaeni (Universitas Sebelas Maret, 2022)
The term good-looking is still used in the labor recruitment process in recent years. Especially in the recruitment of bank employees in Indonesia. Bank employees in Indonesia often get the stereotype that